Evaluation Of Integrated Management Implementation In Hospital In The Health Center Of Sleman D.I Yogyakarta District - Casnuri Casnuri; Puspito Panggih Rahayu (Alma Ata University Press, 2020)
Integrated Management of Sick Toddler (MTBS) is an integrated approach whose governance is carried out on sick toddlers with outpatient facilities. MTBS is used as a service standard for sick infants and toddlers as well as a guideline for nursing staff (midwives and nurses) especially in primary health care facilities. In 2006 the MTBS program socialization and training for puskesmas staff were conducted, where each puskesmas was represented by 1 medical staff and 2 paramedics. MTBS aims to reduce morbidity and mortality due to diarrhea, pneumonia, DHF and infections. IMR in Sleman Regency is better than the national target. In 2015 there were 14,134 live births and 51 (3.61%) stillbirths. This tends to decrease from 2014 when the number of live births was 14,406 with 67 infant deaths (4.65%). The death was caused by diarrhea, pneumonia, DHF and infections. This shows that there is still a need to increase the role of cross-program and cross-sectoral efforts to reduce infant mortality, which is to evaluate the implementation of IMCI or MTBM in the Sleman D.I Yogyakarta Public Health Center.Research Purpose investigate the factors in the implementation of IMCI at the Sleman D.I Yogyakarta Public Health Center.Research Methods is descriptive qualitative. The main Informantts were 25 MTBS officers, 25 Puskesmas heads, and 1 Kasie Kesga District Health Office, Sleman D.I Yogyakarta with in-depth interviews.Research result: All puskesmas in Sleman Regency have implemented MTBS services according to service procedures with different achievements in each puskesmas. This is due to the disorderly officers in conducting data recapitulation. The achievement of the MTBS program in Sleman Regency was 65.39%.Conclusion: The MTBS program at the Sleman district health center has been implemented well due to several factors, namely Human Resources, both the number of trained health workers and the quality of the competencies of health workers, leadership support in the form of facilities and infrastructure, as well as funding support in increasing competence.